Specific and Sensitive Nutrition Interventions with Nutritional Status of Toddlers as Prevention of Stunting in the Coronavirus Disease 2019 Pandemic in Sigi District, Indonesia - Candriasih, Putu; Ndama, Metrys; Pont, Anna Veronica (Open Access Macedonian Journal of Medical Sciences, 2021)
Objective: The research objectives were to determine the specific and sensitive intervention model in stunting prevention efforts in the COVID 19 pandemic. Also, to determine the relationship between specific and sensitive interventions on children’s nutritional status under five in the COVID-19 pandemic in Stunting Locus Village. Method: This type of research was an observational study with a cross-sectional approach. The population and sample in this study were 35 families with stunting children under five. This study used the chi-square test (p-value <α = 0.05) with SPSS computer software. Results: Nutritional status based on the body-weight/age index, 63% was very underweight and underweight. Based on body-height/age, 28.6% was stunted. Based on body-weight/body-height, 17.1% was severe malnutrition and 40.0 % was malnutrition. The results of the bivariate analysis for specific nutrition interventions with body-weight/age showed p = 0.98, body-weight/age had p = 0.668, body-height/age had p = 0.968, which indicated no significant relationship. Conclusions: Sensitive nutrition intervention showed no relationship between sensitive intervention and children’s nutritional status under five